2008
DOI: 10.1016/j.intfin.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Bank-specific, industry-specific and macroeconomic determinants of bank profitability

Abstract: The aim of this study is to examine the effect of bank-specific, industry-specific and macroeconomic determinants of bank profitability, using an empirical framework that incorporates the traditional Structure-Conduct-Performance (SCP) hypothesis. To account for profit persistence, we apply a GMM technique to a panel of Greek banks that covers the period 1985-2001. The estimation results show that profitability persists to a moderate extent, indicating that departures from perfectly competitive market structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

207
1,447
16
42

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,559 publications
(1,839 citation statements)
references
References 43 publications
207
1,447
16
42
Order By: Relevance
“…Beltratti and Stulz (2012), incorporating measures of both bankspecific and country-specific institutional and governance factors, also show that the largest factors of profitability remained bank-specific, including total assets. In addition, Athanasoglou et al (2008) find that capital adequacy and credit risk are also important determinants of bank profitability (adequacy positively and credit risk negatively), and these are also included as explanatory variables. Finally, given the importance of foreign banks for developing the financial sector in transition, I include a dummy for foreign ownership, justified by the empirical results from Claessens et al (2001).…”
Section: The Data and Empirical Modelmentioning
confidence: 98%
See 3 more Smart Citations
“…Beltratti and Stulz (2012), incorporating measures of both bankspecific and country-specific institutional and governance factors, also show that the largest factors of profitability remained bank-specific, including total assets. In addition, Athanasoglou et al (2008) find that capital adequacy and credit risk are also important determinants of bank profitability (adequacy positively and credit risk negatively), and these are also included as explanatory variables. Finally, given the importance of foreign banks for developing the financial sector in transition, I include a dummy for foreign ownership, justified by the empirical results from Claessens et al (2001).…”
Section: The Data and Empirical Modelmentioning
confidence: 98%
“…Bulgaria, 2006Bulgaria, -2012 transition, with work such as Brunetti et al (1997), Havrylyshyn and van Rooden (2003), and Hartwell (2013) taking a methodical look at the various institutions needed for a market economy and how they impacted different parts of the real economy in transition. Linking these two strands of research together is the diverse body of work on how institutions would influence financial outcomes: in addition to Demirgüç-Kunt et al (2004) and Athanasoglou et al (2008), very recent work from Fang et al (2014) has already found some evidence of the impact of institutions on bank stability in transition. Given this empirical backing, it is plausible to expect that these same institutional changes may have benefitted the banking sector writ large and individual banks in particular.…”
Section: Bank Profitability In Transition: the Role Of Institutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Menurut tingkat profitabilitas bank syariah yang diukur dengan laba bersih usaha dapat dipengaruhi oleh kinerja keuangan bank dan juga kondisi makroekonomi yang terjadi dalam perekonomian. 2 Dalam pengertian yang sama menurut Athanasoglou, et.al (2005), menyatakan bahwa profitabilitas bank merupakan fungsi dari faktor internal dan eksternal. 3 Faktor internal merupakan faktor mikro atau faktor spesifik bank yang menentukan profitabilitas.…”
Section: Pendahuluanunclassified